PENGATURAN PENDAFTARAN TANAH ULAYAT DALAM UPAYA MENDUKUNG TERTIB ADMINISTRASI PERTANAHAN - Kurnianti, Dian; Warman, Kurnia; Nurdin, Zefrizal (Ensiklopedia of Journal, 2024)
The Law Number 11 of 2020 on Job Creation (currently amended by Law Number 6 of 2023 on the Determination of Government Regulations in Lieu of Law Number 2 of 2022 on Job Creation becoming Law) is accompanied by its implementing regulations, Government Regulation Number 18 of 2021 on Management Rights, Land Rights, Apartment Units, and Land Registration, as well as Minister of Agrarian and Spatial Planning/Head of the National Land Agency Regulation Number 18 of 2021 on Procedures for Determining Management Rights and Land Rights. These regulations state that the designation of ulayat rights as management rights is a form of recognition of customary law communities. The granting of management rights to customary law communities indirectly makes ulayat land one of the objects of land registration. Currently, the Ministry of Agrarian and Spatial Planning has made efforts through collaboration with the Ministry of Home Affairs, local governments, and universities to implement a pilot project for the determination of management rights on ulayat land. From this pilot project, 6 (six) certificates of management rights on ulayat land have been issued, but as of now, there are no technical regulations related to the determination of management rights on ulayat land. This study will examine the regulatory vacuum and several factors that need to be considered in the formulation of technical regulations for the registration of ulayat land in an effort to support orderly land administration.Keywords: Land Registration, Customary Land, Customary Law Communities, Management Rights